Back to the lake - Cooley, Thomas (W.W.Norton & Company, 2015)
Back to the Lake 3e includes new chapters on writing paragraphs and using rhetorical modes in academic writing―which shows how the patterns taught in this book are used in the kinds of writing college students are expected to do. New readings are on timely topics that will engage students. Templates and marginal notes that explicitly link the readings and the writing instruction help students apply the lessons in this book to their own writing